Bisphenol S impairs oocyte quality by inducing gut microbiota dysbiosis - Jiaming Zhang; Xiaoxia Yu; Weidong Li; Yunjing Jiang; Liangran Zhang; Shunxin Wang (mSystems)
ABSTRACT A good quality egg is essential for a successful pregnancy and early embryo development. Oocyte development is vulnerable to environmental exposures. Bisphenol S (BPS) is widely used as a replacement for its analog bisphenol A, but the reproductive toxicity of BPS has been of great concern. In this study, we showed that BPS exposure induces dysbiosis of the gut microbiota, which further leads to intestinal permeability and inflammation, and ultimately impairs oocyte quality. More importantly, we found that alginate oligosaccharide reshapes the gut microbiota to improve gut homeostasis, thereby preventing the deleterious effects of BPS on the gut and oocytes. Overall, this study not only demonstrates that BPS exposure impairs the intestine and oocytes by inducing dysbiosis of the gut microbiota but also develops a preventive strategy.IMPORTANCEOocyte development is vulnerable to stimulation by intrinsic and extrinsic factors, particularly many environmental pollutants and chemicals in daily life. The reproductive toxicity of bisphenol S has been of great concern, although it is widely used as a safe substitute for its analog bisphenol A. However, it is not known how bisphenol S impairs oocyte quality. This work presents the exciting finding that bisphenol S induces gut microbiota dysbiosis, which further leads to increased intestinal permeability and inflammation and ultimately damages oocytes. More importantly, we show that alginate oligosaccharide improves gut homeostasis by reshaping the gut microbiota, therefore preventing the bisphenol S-induced gut microbiota dysbiosis and gut and oocyte damage. These findings present a major advance in the understanding of bisphenol S toxicity to oocytes and also provide a preventive strategy.